(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
In this article, it is mentioned about the development of potential teachers ’ compensation in the standards of international assessment programs. Also, the author presents proposals and recommendations on the development of the corporate system, stages and pedagogical model of the development of socio-cultural competence in future teachers